Evaluating the effect of Matricaria chamomilla and Melissa officinalis on pain intensity and satisfaction with pain management in patients after orthopedic surgery - Reza Saidi; Haydeh Heidari; Morteza Sedehi; Behrouz Safdarian (Shahrekord University of Medical Sciences, 2020)
Introduction: The most important compliant of post-operative orthopedic patients is severe and intolerable pain. This pain has negative impacts on patient's satisfaction with pain management and bone healing after surgery. This study was conducted with the aim of evaluating the effects of Melissa officinalis (Melissa) tea and Matricaria chamomilla (Chamomile) tea on pain intensity and satisfaction with pain management in patients after lower limb orthopedic surgery. Methods: This was a randomized controlled trial conducted on 96 patients after lower limb orthopedic surgery in Ayatollah Kashani hospital of Shahrekord city, Iran. Patients were randomized to M. officinalis, Chamomile and control groups with blocking randomization method. For M. officinalis group, 1 g of Melissa tea, for Chamomile group 1 g chamomile tea and for control group black tea was prescribed 3 times a day. Study variables were evaluated before and 30 min after each stage of intervention and then the mean changes of pain intensity and satisfaction before interventions and after each step of intervention were compared between groups. Significance level was considered as P<0.05. Results: Before intervention, the mean scores of pain intensity and satisfaction with pain management had no significance difference between groups. The mean changes of pain intensity and satisfaction with pain management (after first 3 steps of intervention) in M. officinalis and M. chamomilla groups were significantly greater than the ones in control group (P<0.05). Conclusion: Prescription of M. officinalis tea or Chamomile tea might be used as effective remedy for reducing pain and increasing satisfaction with pain management after orthopedic surgery.